Matnyak S.V. The proof of the correctness of the conjecture of the Birch and Swinnerton-Dyer. - Матняк, С.В. (Problems of Tribology, 2014)
The proof of the conjecture of the Birch and Swinnerton-Dyer presents in the paper. The Riemann’s hypothesis on the distribution of non-trivial zeros of the zeta̶ function of Riemann, previously proven, using to prove this hypothesis. The theorem proved about the behavior of the -function curve for . It is shown that the -function of the curve tends to zero for any prime unpaired integers. It is shown that the function can be expanded in a power series of the holomorphic field. The theorem proved on conformity of the basis of the Galois group and the number of zero coefficients of the power series. The result proved the conjecture of Birch and Swinnerton-Dyer.